2022
DOI: 10.3390/toxins14110724
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Phospholipase A2 and Metalloproteinases to the Synergistic Action of Viper Venom on the Bioenergetic Profile of Vero Cells

Abstract: Increasing concern about the use of animal models has stimulated the development of in vitro cell culture models for analysis of the biological effects of snake venoms. However, the complexity of animal venoms and the extreme synergy of the venom components during envenomation calls for critical review and analysis. The epithelium is a primary target for injected viper venom’s toxic substances, and therefore, is a focus in modern toxinology. We used the Vero epithelial cell line as a model to compare the actio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Notably, the inhibition of mitochondrial respiration stimulated by glutamate plus malate (complex I’s substrates), succinate (complex II’s substrate), and TMPD (an artificial complex IV’s substrate) plus ascorbate is a previous event for mtDAMPs production [ 90 ]; however, the toxin classes involved remain uncertain. Accordingly, the crude venom of viper Macrovipera lebetina obtusa affects respiration in the Vero monkey kidney epithelial cell line, with this effect sensitive to metalloproteinase and phospholipase inhibitors [ 21 ]. To our knowledge, there are no studies that identify the action of an isolated SVMP on mitochondrial respiration and its implication for the disruptive action of the cell–ECM interaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the inhibition of mitochondrial respiration stimulated by glutamate plus malate (complex I’s substrates), succinate (complex II’s substrate), and TMPD (an artificial complex IV’s substrate) plus ascorbate is a previous event for mtDAMPs production [ 90 ]; however, the toxin classes involved remain uncertain. Accordingly, the crude venom of viper Macrovipera lebetina obtusa affects respiration in the Vero monkey kidney epithelial cell line, with this effect sensitive to metalloproteinase and phospholipase inhibitors [ 21 ]. To our knowledge, there are no studies that identify the action of an isolated SVMP on mitochondrial respiration and its implication for the disruptive action of the cell–ECM interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Some SVMPs also produce intravascular coagulation, edema, inflammation, necrosis, fibrin(ogen) degradation, induction of apoptosis, and inhibition of platelet aggregation [ 8 , 17 , 19 , 20 ]. Recently, a study using crude Macrovipera lebetina obtusa ( Levantine viper ) venom suggested that possibly SVMPs may disrupt the mitochondrial metabolism in the Vero monkey kidney epithelial cell line [ 21 ]. To our knowledge, there are no studies that identify the action of an isolated SVMP on mitochondrial respiration and its implication for the disruptive action of the cell–ECM interaction.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous animal studies have provided supporting evidence that SVMPs, such as Jararhagin, the main SVMP found in the venom of Bothrops asper and Bothrops jararaca , primarily target the basal lamina of alveolar cells, leading to pulmonary hemorrhage [ 50 - 52 ]. The destructive effects on cellular structures can be further intensified by PLA 2 [ 53 , 54 ], another abundant enzyme in venom, as demonstrated by the increased detachment of endothelial cells when both enzymes are present [ 55 ]. Additionally, a C-type lectin (CTL) called aspercetin, which is another venom component, has been identified to potentiate the hemorrhagic effect [ 51 ].…”
Section: Impaired Normal Cell Functions and Integritymentioning
confidence: 99%